PENGARUH PENGELOLAAN KELAS TERHADAP MINAT BELAJAR PKN PADA PESERTA DIDIK DI SMA I POLEWALI - Suhaebah Nur (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
The purpose of this study was to determine the effect on the management of interest in learning civics class at class VIII students of SMA Negeri 1 Polewali . Based on the results of questionnaire analysis of the obtained data is variable X (1328) , the results obtained are 32.32 . Thus, the total score of the average teacher's ability to manage the class during civics lesson quite well. In the questionnaire interest ( Y ) After the total score divided by the number of respondents ( 1328 : 31 ) , the results obtained are 45.83 . Thus, the total score of the average rate of interest of students towards subjects Civics at SMA Negeri 1 Polewali classified as good or are at high criteria . From the analysis of the correlation turned out , .rxy . 4:48 Based on the analysis of correlation variable classroom management or variable X to variable interest in learning civics or variable Y is 4:48 which indicated that between variables X and Y are a very strong correlation.